(untitled) (Biological Sciences - PJSIR, 1999)
Some varieties of dates produced in different parts of Pakistan and the imported popular varieties were assessed for nutrients and minerals. Comparison of the values showed that as far as the common fruit quality characteristics such as proteins, fats and carbohydrates are concerned, there were only slight differences among the indigenous and imported varieties. In some respects, some of the indigenous grown varieties were superior to imported ones while the imported varieties had a slight edge over the locally produced fruit as far as minerals (Na & K) were concerned.